A rapid assessment approach for public health decision-making related to the prevention of malaria during pregnancy - Parise Monica E.; Lewis Linda S.; Ayisi John G.; Nahlen Bernard L.; Slutsker Laurence; Muga Richard; Sharif S.K; Hill Jenny; Steketee Richard W. (The World Health Organization, 2003)
Objective: To develop a rapid field assessment methodology to address the burden of malaria during pregnancy and the options for intervening within the existing antenatal care system in Kenya. Methods: Surveys consisting of questionnaires, sampling of blood for parasitaemia and anaemia, and birth outcome assessment were conducted in antenatal clinics, delivery units, and in the community in Kisumu and Mombasa, Kenya. Findings: The rates of maternal anaemia and severe anaemia, were, respectively, 79% and 8% in Kisumu, and 95% and 24% in Mombasa. The rates of placental parasitaemia were 27% and 24% and the rates of low birth weight were 18% and 24% in Kisumu and Mombasa, respectively. Women with placental parasitaemia had a higher incidence of low birth weight compared with women without placental parasitaemia in both Kisumu (28% vs 16%, P=0.004) and Mombasa (42% vs 20%, P=0.004). A total of 95% and 98% of women in Kisumu and Mombasa, respectively, reported attending an antenatal clinic during their previous pregnancy. Conclusion: This methodology can be used by ministries of health to collect data for decision-making regarding malaria control during pregnancy; it can also provide a baseline measurement on which to evaluate subsequent interventions.